The Impact of Enterprise Risk Management and Sustainability Disclosures on Corporate Value with Corporate Governance as a Moderating Variables - Ganishti, Fairly Sekar; Wennadi, Luky Yunia; Santoso, Hadi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Globalization fosters economic growth and intensifies competition within the business sector, highlighting the increasing importance of information transparency as a source of competitive advantage. Risk disclosures and Sustainability Reports play a pivotal role in enhancing stakeholder trust and boosting firm value through transparency. This study investigates the impact of risk disclosure and Sustainability Report disclosures on firm value, while also exploring the moderating role of Corporate Governance. Using purposive sampling, data from 80 companies listed in the Kompas 100 index in 2022 were analyzed using E-Views software. The findings reveal that risk disclosure positively influences firm value, whereas the disclosure of Sustainability Reports does not significantly affect firm value. Additionally, CG moderates the relationship between risk disclosure and firm value, reinforcing its negative impact, while CG strengthens the positive relationship between Sustainability Report disclosure and firm value. These results offer valuable insights into the role of transparency and governance in shaping corporate outcomes in a globalized market.